#Metoo in the Swedish forest sector: testimonies from harassed women on sexualised forms of male control. Issue 5 (4th July 2018) - Johansson, Maria; Johansson, Kristina; Andersson, Elias
ABSTRACT: This study adds to the literature on the gendered culture of the forest sector by examining testimonies of sexual harassment in relation to the gendering of forestry-related competence and organisations and the consequences that the sexualisation of social relations in organisations has, mainly for women. The empirical base of the study comprised testimonies within the campaign #slutavverkat published on Instagram to highlight experiences of sexual harassment of women in the Swedish forest sector. Qualitative content analysis of the testimonies suggested that the situations described in the testimonies in #slutavverkat comprise controlling actions that diminish women's power in the forest sector. Sexualised forms of male control and harassment thus work to remind women that they are first and foremost a representation of women, rather than of forestry professions and knowledge. In that sense, sexualised forms of male control and harassment are part of, rather than deviating from, the overall gendering of forestry as a men-dominated sphere. The study adds to organisational understandings and policy developments on discrimination and harassment and suggests that researchers and policy-makers interested in reducing inequality in forestry need to pay more attention to issues of harassment and sexualisation of social relations.